Let $\Omega, F, P$ be a probability space and $A, B, D \in F$. If $P( A \mid D ) \ge P(A)$ and $P( B \mid D) \ge P(B)$. Show that if $A \cap B = \emptyset$ then $P(A^c \cap B^c \mid D) \le P(A^c \cap B^c)$.

I know that given that $A \cap B = \emptyset$ then they are mutually exclusives, this means that $P(A \cap B) = 0$

So, $P( A \cup B) = P(A) + P(B)$, and since $P( A \cup B) = 1 - P(A^c \cap B^c)$, this gives:

$P(A^c \cap B^c) = 1 - P(A) - P(B)$

I got an expression for $P(A^c \cap B^c)$ but I don't know how to develop the proof from here, $P(A^c \cap B^c \mid D)$ can be expanded using the Bayes theorem, but this lead's me to nowhere, Im stuck.

  • $\begingroup$ Can you check if the condition is $P(D|A) \geq P(A)$ or $P(A|D) \geq P(A)$? $\endgroup$
    – Zhanxiong
    Dec 3, 2023 at 5:53
  • $\begingroup$ Sorry @Zhanxiong, the condition is $P(A \mid D) \ge P(A)$, im editing the original question. $\endgroup$
    – Occhima
    Dec 3, 2023 at 14:20

1 Answer 1


Using the observation that you have made (i.e., the De Morgan law and the complementary law) shows that it is equivalent to prove \begin{align*} P(A \cup B) \leq P(A \cup B|D). \tag{1}\label{1} \end{align*} The condition $A \cap B = \varnothing$ implies that $(A \cap D) \cap (B \cap D) = \varnothing$, whence \begin{align*} P(A \cup B|D) &= \frac{P((A \cup B)\cap D)}{P(D)} \\ &= \frac{P(A \cap D) + P(B \cap D)}{P(D)} \\ &= P(A|D) + P(B|D) \\ & \geq P(A) + P(B) = P(A \cup B). \end{align*} This completes the proof.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.